2019
DOI: 10.1038/s41598-019-50999-z
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Genome-Wide Variation, Population Differentiation and SNP Discovery of the Red Banded Stink Bug (Piezodorus guildinii)

Abstract: Unravelling the details of range expansion and ecological dominance shifts of insect pests has been challenging due to the lack of basic knowledge about population structure, gene flow, and most importantly, how natural selection is affecting the adaptive process. Piezodous guildinii is an emerging pest of soybean in the southern region of the United States, and increasingly important in Brazil in recent years. However, the reasons P. guildinii is gradually becoming more of a problem are questions still mostly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…We found that P. guildinii displayed a higher intestinal bacterial diversity from Brazil than the United States, which might be mainly explained by genetic and environmental factors. For genetic factors, Zucchi et al (2019a) evidenced distinct P. guildinii lineages from Brazil and the United States using Genotype-By-Sequencing. These genetic differences in stink bug lineages might account for the differences in the intestinal microbiome changing the physicochemical conditions of the intestine and, consequently, the microbial composition of the different lineages.…”
Section: Discussionmentioning
confidence: 99%
“…We found that P. guildinii displayed a higher intestinal bacterial diversity from Brazil than the United States, which might be mainly explained by genetic and environmental factors. For genetic factors, Zucchi et al (2019a) evidenced distinct P. guildinii lineages from Brazil and the United States using Genotype-By-Sequencing. These genetic differences in stink bug lineages might account for the differences in the intestinal microbiome changing the physicochemical conditions of the intestine and, consequently, the microbial composition of the different lineages.…”
Section: Discussionmentioning
confidence: 99%
“…We found that P. guildinii displayed a higher intestinal bacterial diversity from Brazil than the US, which might be explained mainly by genetic and environmental factors. For genetic factors, Zucchi et al [45] evidenced distinct P. guildinii lineages from Brazil and the United States using Genotype-By-Sequencing. These genetic differences in stink bug lineages might account for the differences in the intestinal microbiome.…”
Section: Microbiome Structure and Diversitymentioning
confidence: 99%
“…Molecular resources currently available for RBSB in public databases are limited to 107 microsatellite sequences, six partial cytochrome oxidase I (COI) subunit sequences [25] and 17 Gbp of genotype by sequencing (GBS) data in the NCBI sequence read archive [14]. Transcriptome, genome or proteome data are not available for this species.…”
Section: Main Textmentioning
confidence: 99%
“…Resistance to insecticides in RBSB has been documented but the genetic basis of the insecticide resistance in this insect is not well understood. So far, only one population genetic study has been carried out on this species using 1,337 SNP markers [14] to estimate genetic structure and to identify loci under natural selection. This study identi ed the presence of genetic structure separating populations in USA and Brazil.…”
Section: Introductionmentioning
confidence: 99%